Mobilizing farmers' resources for the maintenance of irrigation systems - Karunasena, H. A. (1993)
The aim of this paper is to illustrate the experience gained in the planning and implementation of management innovations in an irrigation system in Sri Lanka through a participatory action research programme. The areas where the performance of maintenance work can be improved are identified as the financial management and the physical work implementation procedures. Under deficit financial resource conditions farmers' contribution for maintenance work was found to be the most appropriate solution. In addition, the procedural and methodological changes are useful in sustaining the performance of irrigation systems when the resources are limited.